The Holy Grail: A road map for unlocking the climate record stored within Mars' polar layered deposits. (May 2020) - Smith, Isaac B.; Hayne, Paul O.; Byrne, Shane; Becerra, Patricio; Kahre, Melinda; Calvin, Wendy; Hvidberg, Christine; Milkovich, Sarah; Buhler, Peter; Landis, Margaret; Horgan, Briony; Kleinböhl, Armin; et al.
Abstract: In its polar layered deposits (PLD), Mars possesses a record of its recent climate, analogous to terrestrial ice sheets containing climate records on Earth. Each PLD is greater than 2 ​km thick and contains thousands of layers, each containing information on the climatic and atmospheric state during its deposition, creating a climate archive. With detailed measurements of layer composition, it may be possible to extract age, accumulation rates, atmospheric conditions, and surface activity at the time of deposition, among other important parameters; gaining the information would allow us to "read" the climate record. Because Mars has fewer complicating factors than Earth (e.g. oceans, biology, and human-modified climate), the planet offers a unique opportunity to study the history of a terrestrial planet's climate, which in turn can teach us about our own planet and the thousands of terrestrial exoplanets waiting to be discovered. During a two-part workshop, the Keck Institute for Space Studies (KISS) hosted 38 Mars scientists and engineers who focused on determining the measurements needed to extract the climate record contained in the PLD. The group converged on four fundamental questions that must be answered with the goal of interpreting the climate record and finding its history based on the climate drivers. The group then proposed numerous measurements in order to answer these questions and detailed a sequence of missions and architecture to complete the measurements. In all, several missions are required, including an orbiter that can characterize the present climate and volatile reservoirs; a static reconnaissance lander capable of characterizing near surface atmospheric processes, annual accumulation, surface properties, and layer formation mechanism in the upper 50 ​cm of the PLD; a network of SmallSat landers focused on meteorology for ground truth of the low-altitude orbiter data; and finally, a second landed platform to access 500 ​m of layers to measure layer variability through time. This mission architecture, with two landers, would meet the science goals and is designed to save costs compared to a single very capable landed mission. The rationale for this plan is presented below. In this paper we discuss numerous aspects, including our motivation, background of polar science, the climate science that drives polar layer formation, modeling of the atmosphere and climate to create hypotheses for what the layers mean, and terrestrial analogs to climatological studies. Finally, we present a list of measurements and missions required to answer the four major questions and read the climate record.